Features of the Course and Effectiveness of Treatment of Pulmonary Tuberculosis with Drug-Resistant Pathogen (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article describes the methods used at the present stage for the treatment of tuberculosis with multiple drug resistance. A clinical example of treatment of a patient with multidrug category 4 resistance, second-line drugs, the use of which made it possible to achieve clinical improvement, cessation of bacterial excretion and involution of specific changes in the lungs. Efficiency therapy is proven by achieving shorter stabilization of tuberculous inflammation.